Factors Determining to promote SMEs through Technology Management - Valliappan Raju, Assoc. Prof. Dr.; Md Rom Bin Tamjis, Prof Dr. (International Journal of Engineering and Technology, 2019)
The central purpose of this paper is to propose the most appropriate instruction model that is worth implementing in the context of the board of innovation (MoT), especially in situations involving small and medium enterprises (SMEs). Relative to the contemporary local structure characterizing the global pattern change and the Chungcheong context, a central assumption is that three major educational programs play a crucial role towards the preparation of individuals seeking to take up an important role of SME elevation (towards global operation and achievement). These factors include the globalization of advances, the executives of uniting advances, and innovation commercialization.Â Â Â